2020
DOI: 10.47176/mjiri.34.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microRNAs polymorphism in cancer progression

Abstract: ↑What is "already known" in this topic: MicroRNAs (miRNAs) are known as a new class of small RNAs (18-25 nucleotides) which regulate gene expression at multiple levels from transcription to translation. Considering the important role of miRNAs in cell proliferation, differentiation, and apoptosis, any variations in their expression can contribute to various anomalies, such as tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Although miRNAs possess tumor suppressor and oncogene functions in various cancers and are important in carcinogenesis, they also contribute to different cellular biological processes such as cell growth, differentiation, and cell division [ 11 ]. Single-nucleotide polymorphisms (SNPs) in genes encoding miRNAs can adversely affect mature miRNA formation and interaction with target mRNAs, thereby affecting all stages of miRNA biogenesis [ 12 ]. In recent studies, SNPs associated with miRNAs in various diseases have been reported and recommended as candidate genetic biomarkers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although miRNAs possess tumor suppressor and oncogene functions in various cancers and are important in carcinogenesis, they also contribute to different cellular biological processes such as cell growth, differentiation, and cell division [ 11 ]. Single-nucleotide polymorphisms (SNPs) in genes encoding miRNAs can adversely affect mature miRNA formation and interaction with target mRNAs, thereby affecting all stages of miRNA biogenesis [ 12 ]. In recent studies, SNPs associated with miRNAs in various diseases have been reported and recommended as candidate genetic biomarkers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%